Catecholamines in sepsis: pharmacological insights and clinical applications—a narrative review - Jacopo Belfiore; Riccardo Taddei; Giandomenico Biancofiore (Journal of Anesthesia, Analgesia and Critical Care)
Abstract Catecholamines, essential neurotransmitters and hormones, play a critical role in the body’s physiological response to stress and are pivotal in the management of various clinical conditions, particularly in critical care settings. This narrative review delves into the pharmacological properties of catecholamines, including their mechanisms of action, pharmacokinetics, and pharmacodynamics. Key clinical applications of catecholamines, especially in the cardiovascular and immune systems, are highlighted, emphasizing their roles in modulating heart rate, vascular tone, and immune responses during critical conditions such as sepsis and septic shock. Additionally, the review explores catecholamines’ immunomodulatory effects and their interactions with other therapeutic agents, such as corticosteroids, in the management of septic shock. Further research is suggested to optimize catecholamine usage and improve patient outcomes in critical care settings.